Melt electrowriting of bioglass-laden poly(ϵ-caprolactone) scaffolds for bone regeneration - de Carvalho, Ana Beatriz Gomes [UNESP]; Cardoso, Lais Medeiros [UNESP]; Anselmi, Caroline [UNESP]; Dal-Fabbro, Renan; Campos, Tiago Moreira Bastos; Borges, Alexandre Luiz Souto [UNESP]; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Bottino, Marco C. (Royal Society of Chemistry (RSC), 2025)
Novel and promising biomaterials for bone tissue engineering have been investigated over the years. Aiming to contribute to this progress, this study developed and evaluated polycaprolactone (PCL) scaffolds with 5% (w/w) 58S-bioactive glass (58S-BG) fabricated via melt electrowriting (MEW). Morphological and chemical characterization of the scaffolds was conducted. The biological potential was assessed in vitro with alveolar bone-derived mesenchymal stem cells through cytotoxicity, adhesion, protein production, alkaline phosphatase activity, and mineral nodule formation assays. In vivo, scaffolds implanted in rats were analyzed for biocompatibility, inflammation, and degradation using H&E staining and immunohistochemical markers for angiogenesis and macrophage polarization. Statistical analysis was performed at a 5% significance level. Appropriate fiber alignment but a higher fiber diameter was found for PCL + BG5% compared to PCL scaffolds (p = 0.002). EDS spectra confirmed the presence of BG's chemical components for BG-laden scaffolds, attesting to BG particle incorporation into the filaments. Raman spectroscopy evidenced the chemical nature of the BG powder, and FTIR spectra revealed -OH stretching for PCL + BG5%, evidencing its hydrophilic potential. None of the scaffolds were cytotoxic, and BG-laden formulation increased cell viability after 7 days (p = 0.0006), also showing greater cell adhesion/spreading over time compared to pristine PCL scaffolds. BG's presence also increased the mineral matrix formation (p ≤ 0.0021) over 21 days and retained ALP activity after 14 days (p = 0.705) compared to PCL. In vivo, PCL scaffolds retained fiber alignment and preserved their volume throughout the evaluation, showing minimal structural alteration. In contrast, PCL + BG5% scaffolds showed more visible structural changes at 28 days. Despite this, the PCL + BG5% formulation remained biocompatible and significantly promoted angiogenesis compared to pristine PCL scaffolds. In sum, BG-laden scaffolds were successfully melt electrowritten, retaining the scaffolds’ porous architecture, showing appropriate properties, including cell viability, adhesion, mineralized nodule deposition, biocompatibility, and angiogenesis, indicating that these materials are a promising alternative for enhancing bone tissue regeneration.